Investigating the Effect of Acupressure on the Patients' Anxiety Before Open-Heart Surgery: A Randomized Clinical Trial - Bagher Khoram; Amin K. Yoosefinejad; Mozhgan Rivaz; Seyed S. Najafi (Medical Association of Pharmacopuncture Institute, 2020)
Background: Anxiety is a common complaint of patients before diagnostic or therapeutic invasive procedures, especially before open-heart surgery. The most well-known method to reduce anxiety is the use of sedatives, which have pronounced side effects. Objectives: The purpose of this study was to determine the effect of acupressure on anxiety in patients undergoing open-heart surgery. Method: This is a randomized clinical trial study conducted on 90 patients who were candidates for open-heart surgery. The patients were randomly assigned into either intervention or control groups. Acupressure intervention was applied at three real acupoints over two consecutive days in the intervention group. The control group received acupressure on sham points. We used Spielberger State-Trait Anxiety Inventory to assess anxiety in our study. Results: The results showed that before acupressure, there was no statistically significant difference between state anxiety scores and intergroup traits, and this difference was only significant in state anxiety after the second intervention. State and trait anxiety were significant before and after the intervention in the test group, respectively include (p < 0.001) (p = 0.01), but these changes in the control group did not show a statistically significant difference. After completing the second phase of the intervention at the actual sites, systolic blood pressure (p = 0.007) and heart rate (p = 0.001) decreased significantly. However, acupressure did not have a significant effect on diastolic blood pressure in any of the groups. Conclusion: Based on the results of this study, the application of acupressure in patients who are candidates for open-heart surgery can reduce their state anxiety. Further larger-scale and rigorous studies are warranted.